A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages with other health services, and their distribution is uneven. They have grown up without a national or even an area plan. In one area there may be already established a variety of good hospitals. Another area, although the need is there, is sparsely served. One hospital may have a long waiting list and be refusing admission to cases which another hospital not far away could suitably accommodate and treat at once. There is undue pressure in some areas on the hospital out-patient departments — in spite of certain experiments which some of the hospitals have tried (and which should be encouraged) in arranging a system of timed appointments to obviate long waiting. Moreover, even though most people have access to a hospital of some kind, it is not necessarily access to the right hospital. The tendency in the modern development of medicine and surgery is towards specialist centres — for radio-therapy and neurosis, for example — and no one hospital can be equally equipped and developed to suit all needs, or to specialise equally in all subjects. The time has come when the hospital services have to be planned as a wider whole, with the object of securing that each case shall be referred, not necessarily to the particular hospital which happens to be "local," but to whatever hospital can offer the most up-to-date technique for that kind of case. To achieve this object and to remedy the present lack of coherence, there is need of a single authority which has the duty to secure for the area for which it is responsible a complete hospital service. The unit of administration At present, hospital services which are publicly provided are mainly in the hands of county and county borough councils. The Government have no desire to disturb unnecessarily the present form of local government organisation or to interfere without cause in the work of these major local authorities. Indeed, it is their intention to base the local organisation of the new Health Service generally on these major authorities, operating over their own areas where possible and combining in larger joint areas only where necessary. But it is abundantly clear that, with a few exceptions, counties and county boroughs are not large enough to serve as the area on which a unified hospital service could be based. For the purpose an area must fulfil three conditions :— (a) Its population and financial resources must be sufficient to make possible an adequate, efficient and economical service. (b) It should normally include both urban and rural areas so that the needs of town and country can be properly balanced. (c) It should be such that most of the varied hospital and specialist services can be organised within its boundaries in a self-sufficient scheme (leaving for inter-area arrangement only certain specialised services). In the great majority of the counties and county boroughs these three conditions would not be met. The Government therefore propose that responsibility for the new 13 36/H24/41